2022
DOI: 10.3390/en15092973
|View full text |Cite
|
Sign up to set email alerts
|

Free Vibrations of Flexoelectric FGM Conical Nanoshells with Piezoelectric Layers: Modeling and Analysis

Abstract: Flexoelectric and piezoelectric effects have attracted the attention of researchers, owing to their applications in sensing systems and actuators. In this paper, the vibration of functionally graded material (FGM) conical nanoshell is studied, taking into account both piezoelectricity and flexoelectricity. The nanoshell has a sandwich-type structure with a FGM core and two layers of piezoelectric materials on its top and bottom. With the combination of the first order shear deformation and Eringen’s nonlocal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Related research has been reported on engineering structures such as beams, plates, and rings from both theoretical and experimental perspectives (Fan et al, 2018; Hu et al, 2011; Tzou et al, 2017; Zhang et al, 2016). The vibration of functionally graded material (FGM) conical nanoshell is studied, and the vibration equation of the nanoshell is developed with the combination of the first order shear deformation and Eringen’s nonlocal theories (Khorshidi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Related research has been reported on engineering structures such as beams, plates, and rings from both theoretical and experimental perspectives (Fan et al, 2018; Hu et al, 2011; Tzou et al, 2017; Zhang et al, 2016). The vibration of functionally graded material (FGM) conical nanoshell is studied, and the vibration equation of the nanoshell is developed with the combination of the first order shear deformation and Eringen’s nonlocal theories (Khorshidi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%